FUNGSI TUNGKU TIGO SAJARANGAN DALAM UPAYA PEMBANGUNAN SUMBER DAYA MANUSIA NAGARI PARIANGAN DI KECAMATAN PARIANGAN KABUPATEN TANAH DATAR TAHUN 2023 - M, Abdhi Alhafiz.; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Government Functions are the important roles played by government institutions in carrying out their functions to meet the needs of society. Government functions include a series of activities carried out by various government institutions to create an orderly social order, provide services to the community, and manage resources. The function of Tungku Tigo Sajarangan based on Regional Regulation Number 7 of 2018 concerning Nagari Tungku Tigo Sajarangan is leadership that is interrelated and has an important role in the wheel of traditional, religious and knowledgeable leadership. Tungku Tigo Sajarangan is the collective leadership of the Minangkabau people. This research aims to examine the function of the Tigo Sajarangan Furnace in efforts to develop human resources in Nagari Pariangan in Pariangan District, Tanah Datar Regency in 2023. Thus, in the process of completing this research, the researcher used a qualitative approach with data collection techniques through interviews and documentation. The interview was conducted with Tungku Tigo Sajarangan consisting of Niniak Mamak, Alim Ulama, Cadiak Pandai, Wali Nagari Pariangan, Wali Jorong Pariangan, Pariangan Community and other Nagari officials. The findings show that the Tigo Sajarangan Furnace has performed its function well with efforts to improve the quality of Human Resources in Nagari Pariangan, as follows: 1. The function of Government Administration is to determine the Nagari's future direction, especially in terms of development 2. Development function to develop Nagari from a physical and non-physical perspective so that no Human Resources are left behind in Nagari Pariangan 3. Service function to serve the community in Nagari Pariangan regarding existing policies in Nagari 4. Protection function to guide the community in Nagari Pariangan regarding customs, science and religion Keywords: Government Functions, Tigo Sajarangan Furnace, Human ResourceDevelopmen